Linking size‐dependent growth and mortality with architectural traits across 145 co‐occurring tropical tree species. Issue 2 (1st February 2014) - Iida, Yoshiko; Poorter, Lourens; Sterck, Frank; Kassim, Abd Rahman; Potts, Matthew D.; Kubo, Takuya; Kohyama, Takashi S.
Abstract : Tree architecture, growth, and mortality change with increasing tree size and associated light conditions. To date, few studies have quantified how size‐dependent changes in growth and mortality rates co‐vary with architectural traits, and how such size‐dependent changes differ across species and possible light capture strategies. We applied a hierarchical Bayesian model to quantify size‐dependent changes in demographic rates and correlated demographic rates and architectural traits for 145 co‐occurring Malaysian rain‐forest tree species covering a wide range of tree sizes. Demographic rates were estimated using relative growth rate in stem diameter (RGR) and mortality rate as a function of stem diameter. Architectural traits examined were adult stature measured as the 95‐percentile of the maximum stem diameter (upper diameter), wood density, and three tree architectural variables: tree height, foliage height, and crown width. Correlations between demographic rates and architectural traits were examined for stem diameters ranging from 1 to 47 cm. As a result, RGR and mortality varied significantly with increasing stem diameter across species. At smaller stem diameters, RGR was higher for tall trees with wide crowns, large upper diameter, and low wood density. Increased mortality was associated with low wood density at small diameters, and associated with small upper diameter and wide crowns over a wide range of stem diameters. Positive correlations between RGR and mortality were found over the whole range of stem diameters, but they were significant only at small stem diameters. Associations between architectural traits and demographic rates were strongest at small stem diameters. In the dark understory of tropical rain forests, the limiting amount of light is likely to make the interspecific difference in the effects of functional traits on demography more clear. Demographic performance is therefore tightly linked with architectural traits such as adult stature, wood density, and capacity for horizontal crown expansion. The enhancement of a demographic trade‐off due to interspecific variation in functional traits in the understory helps to explain species coexistence in diverse rain forests.